Metode Think-Pair-Share Dengan Analisis Artikel Untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi Mahasiswa - Hikmawati Hikmawati; Haerunisyah Sahidu; Syahrial Ayub (Kappa Journal, 2021)
The purpose of this study was to describe the application of the think-pair-share method with article analysis to improve students' higher order thinking skills. This type of research is pre-experimental with research subjects, namely students who take the Physics Learning Strategy course, academic year 2020/2021, at one of the universities in Mataram, totaling 27 people. The research design used was One Group Pre-test and Post-test Design. The instrument used in this study was a test of higher order thinking skills. The level of higher order thinking skills of students is calculated as a percentage, with 5 categories. The increase in score is calculated using N-gain, with 3 criteria. The results showed that the level of high-order thinking skills of students at the pre-test was 49 with a very low category, while at the time of the post-test it was 83 in the good category. The N-gain score is 68 with moderate criteria. Thus, the application of the think-pair-share method with article analysis can improve students' higher-order thinking skills in the Physics Learning Strategy course.